AN OUTBREAK OF SEVERE PNEUMONIA DUE TO RESPIRATORY SYNCYTIAL VIRUS IN ISOLATED ARCTIC POPULATIONS - MORRELL, R. E.; MARKS, M. I.; CHAMPLIN, R.; SPENCE, L. (Oxford University Press, 1975)
A rapidly developing outbreak of pneumonia in young infants was documented in two isolated Arctic populations in May 1972. These were studied virologically, serologically and clinically. In addition to the two stricken communities, one apparently unaffected with serious clinical illness and a fourth, in which are located the major hospital and airport in the eastern Arctic, were also studied. One hundred and twenty-four patients were studied serologically and 81 respiratory and other specimens were obtained for virus isolation from 40 of these patients. Clinical records were kept of the outbreak in each area and a detailed questionnaire was filled out for 140 children and their families. Respiratory syncytial virus (RSV) was cultured from eight ill children. Electron microscopy provided the first evidence of RSV infection. A seroconversion rate of approximately 50% was seen in both affected communities as well as in the clinically unaffected one. The epidemic in the first two communities was characterized by severe pneumonia and frequent hospitalization but no cases of bronchiolitis were seen. No evidence for other causes of this outbreak could be obtained by testing for antibodies to influenza A and B, parainfluenza 1, 2 and 3, adenovirus and herpes simplex viruses. Unusual features of this epidemic of RSV infection include the high attack rate, severe morbidity, illness manifest almost exclusively as pneumonia rather than bronchiolitis and the differences between the expression of disease in different communities. Historical data and clinical observations were inadequate to explain these unusual features.